Bird's electrical and electronic principles and technology - Bird, J. O. (Routledge, 2021)
"This practical Level 2 and 3, foundation degree and year 1 undergraduate textbook introduces essentials through detailed examples and laboratory experiments. Now with glass batteries, climate change and the future of electricity production. Its rich companion website includes multiple choice tests and 900 questions and solutions"--